LEXICAL-SEMANTIC COMPARISON OF KINSHIP TERMS IN ENGLISH AND UZBEK LANGUAGES (Ustozlar uchun, 2026)
Kinship systems are basic and ancient components of human culture, reflecting family relations, social hierarchies, traditions, and worldview. Every nation and each language community forms its kinship vocabulary in line with historical development, cultural values, and specific social needs. English and Uzbek, as representatives of Indo-European and Turkic language families respectively, display certain similarities as well as significant differences in their kinship lexicon. The lexical-semantic comparison of kinship terms provides an opportunity to reveal not only the structural features of the two languages but also the factors underlying their cultural mentality and social organization.